Nail growth arrest under low body temperature during hibernation - Taiga Ishimoto; Hideyuki Kosumi; Ken Natsuga; Yoshifumi Yamaguchi (Journal of Physiological Sciences)
Abstract Growth and differentiation are reduced or stopped during hibernation, an energy conserving strategy in harsh seasons by lowered metabolism and body temperature. However, few studies evaluated this in a same individual using a non-invasive method. In this study, we applied a non-invasive tracking method of the nail growth throughout the hibernation period in the same hibernating animals, the Syrian hamster (Mesocricetus auratus). We found that nail growth was markedly suppressed during the hibernation period but rapidly recovered by the exit from the hibernation period. Our data suggest that nail growth was arrested during deep torpor, a hypometabolic and hypothermic state, but recovered during periodic arousal, a euthermic phase. Consistent with this, nail stem cells located in the nail matrix did not exit the cell cycle in the deep torpor. Thus, hibernation stops nail growth in a body temperature-dependent manner.